2000
DOI: 10.1891/0886-6708.15.3.283
|View full text |Cite
|
Sign up to set email alerts
|

Coping With Chronic Community Violence: The Variety and Implications of Women’s Efforts

Abstract: To date, most researchers concerned with chronic community violence have studied children, and focused on the types, extent, and effects of their violence experiences. In contrast, using a series of in-depth repeated interviews, the current study explored African American women’s methods for coping with chronic community violence. This article describes the variety of ways these women developed to avoid, minimize, or manage their own and their children’s encounters with community violence. It argues for the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…The emergent coping themes from this study both extend and corroborate those found in a qualitative study of Black women residing in Chicago housing project (Wolfer, 2000) and a quantitative study of multiethnic sixth graders (Rosario et al, 2003). These prior studies did not identify confrontational coping styles such as "getting back" among their respondents.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The emergent coping themes from this study both extend and corroborate those found in a qualitative study of Black women residing in Chicago housing project (Wolfer, 2000) and a quantitative study of multiethnic sixth graders (Rosario et al, 2003). These prior studies did not identify confrontational coping styles such as "getting back" among their respondents.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, the coping strategy of confrontation was only discussed by the boys. This is an especially interesting finding because getting back or confrontation has not been viewed in prior literature as a coping mechanism (Rosario et al, 2003;Wolfer, 2000).…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, Brodsky (1999) notes that the ability to generate strategies for maintaining 'psychological distance' from negative associations, where geographical separation is unattainable, is associated with successful survival by women in highly distressed neighbourhoods. Thus, Wolfer (2000) investigated women's efforts to cope with chronic violence in high-risk neighbourhoods. According to their appraisal of specific violent situations, women selectively employed a diverse repertoire of problem-focused strategies, designed to avoid dangerous areas and individuals and manage interpersonal relationships to reduce risk, as well as emotion-focused strategies for distraction from anxietyprovoking stimuli and self-soothing.…”
Section: Personal Resiliencementioning
confidence: 99%
“…Studies of coping in conditions of adversity have commonly distinguished between problem-focused and emotion-focused strategies (Wolfer 2000;Yoshihama 2002). In the context of negotiating the 'daily hassles' of mundane existence, active coping strategies are generally more likely to moderate the deleterious effects of stress on psychological well-being than attempts to suppress or ignore the problems (Lu 1991).…”
Section: Personal Resiliencementioning
confidence: 99%
“…They, too, stay indoors, during the day and at night. 5,11 They may run errands in the morning or on weekends, when gunfire is less common. 6,7,12 The Centers for Disease Control and Prevention (CDC) has advised entire communities to remain indoors at times of particular risk.…”
mentioning
confidence: 99%